THE ECHO OF THE PERSON IN THE HARMONY OF THE COSMOS: MAN IN CHINESE PHILOSOPHY1 - Dariusz Klejnowski-Różycki; Maria Bernat (Studia Theologica Varsaviensia, 2025)
Man in Chinese philosophical and artistic traditions is presented as deeply embedded within social, cosmic, and spiritual orders. Unlike the Western notion of the autonomous „person,” rooted in individuality and substantiality, Chinese thought focuses on relationality and harmony. Confucianism views man as a social being whose identity emerges through fulfilling relationships and roles within the community. Taoism emphasizes man’s unity with nature, portraying him as a small element in the larger cosmos, striving for harmony with dao. Buddhism transcends earthly existence, presenting man as a seeker of enlightenment and spiritual liberation. Chinese art complements these philosophical insights. Taoistinspired works depict man as a part of majestic natural landscapes, blending into their surroundings. Confucian art reflects man’s social interactions, symbolizing community and spiritual unity. Buddhist representations focus on the transcendental, with temples and mystical imagery underscoring spiritual aspirations. These perspectives highlight fundamental differences between Western individualism and Eastern relationality, offering complementary insights into humanity’s nature.